Mental Illness, Natural Death, and Non-Voluntary Passive Euthanasia - Varelius, Jukka (2016)
When it is considered to be in their best interests, withholding and withdrawing life-supporting treatment from non-competent physically ill or injured patients - non-voluntary passive euthanasia, as it has been called - is generally accepted. A central reason in support of the procedures relates to the perceived manner of death they involve: in non-voluntary passive euthanasia death is seen to come about naturally. When a non-competent psychiatric patient attempts to kill herself, the mental health care providers treating her are obligated to try to stop her. Yet it has been suggested that death by suicide can be a part of the natural course of a severe mental illness. Accordingly, if the perceived naturalness of the deaths occurring in connection with non-voluntary passive euthanasia speaks for their moral permissibility, it could be taken that a similar reason can support the moral acceptability of the suicidal deaths of non-competent psychiatric patients. In this article, I consider whether the suicidal death of a non-competent psychiatric patient would necessarily be less natural than those of physically ill or injured patients who die as a result of non-voluntary passive euthanasia. I argue that it would not.
Keywords: Death; Mental Illness; Passive Euthanasia; physician-assisted suicide; Psychiatry